Fenomena Resign Massal dan Pengangguran Terselubung di Kalangan Gen Z: Tinajuan Ekonomi Publik di Indonesia - Silvy Novianty; Assyfa Futri Ananta; Viola Augustia Putri; Wahjoe Pangestoeti (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2025)
The phenomenon of mass resignations and the rise of disguised unemployment among Generation Z in Indonesia raises concerns about the sustainability of national employment. This study aims to analyze this phenomenon within the framework of public economics by exploring its causes and impacts on productivity and labor market structure. Employing a qualitative approach through literature review, the research finds that the main causes include the mismatch between education and labor market demands, a crisis of work meaning, and changing social values among the younger generation. This phenomenon is also related to the trend of quiet quitting, characterized by passive work attitudes while remaining in the job. The findings underscore the necessity for adaptive public economic policies that respond to the evolving work values of younger generations, as well as more flexible and inclusive employment strategies in the digital era.